2019
DOI: 10.1002/pen.25186
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial adhesion and water resistance of stainless steel–polyolefin improved by functionalized silane

Abstract: The adhesion strength and water resistance of stainless steel and adhesive resin composites determine the longterm performance of wires and cables; however, adhesion at stainless steel interfaces is difficult. Herein, we prepared ethylene acrylic acid/linear low-density polyethylene (EAA/LLDPE) blends with good mechanical and adhesive properties. Silane was anchored to the surface of stainless steel. The effects of silane functionalization on the adhesion surface were investigated by X-ray photoelectron spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…HMAs generally consists of three main components: polymer base, tackifier, and plasticizer, but may contain other additives. [ 6,7 ] The most widely used polymer bases are polyethylene [ 8,9 ] and ethylene copolymers (poly(ethylene‐co‐vinyl acetate), poly(ethylene‐co‐ethyl acrylate), poly(ethylene‐co‐acrylic acid) [ 2,10‐12 ] ), polyisoprene, [ 13 ] polyester, [ 14 ] poly(vinyl acetate), [ 15 ] polyisobutylene, [ 16,17 ] polyamide, [ 18 ] polyurethane, [ 19,20 ] and polylactide. [ 21 ] The polymer base is composes more than half of the adhesive and is responsible for its strength, elasticity, viscosity, and adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…HMAs generally consists of three main components: polymer base, tackifier, and plasticizer, but may contain other additives. [ 6,7 ] The most widely used polymer bases are polyethylene [ 8,9 ] and ethylene copolymers (poly(ethylene‐co‐vinyl acetate), poly(ethylene‐co‐ethyl acrylate), poly(ethylene‐co‐acrylic acid) [ 2,10‐12 ] ), polyisoprene, [ 13 ] polyester, [ 14 ] poly(vinyl acetate), [ 15 ] polyisobutylene, [ 16,17 ] polyamide, [ 18 ] polyurethane, [ 19,20 ] and polylactide. [ 21 ] The polymer base is composes more than half of the adhesive and is responsible for its strength, elasticity, viscosity, and adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [ 139 ] report a method to improve the adhesion strength and water resistance of stainless steel and ethylene acrylic acid/linear low-density polyethylene (EAA/LLDPE) blend film composites by using functionalized silane as a surface modifier. They found that the EAA/LLDPE (60:40) blend had the best balance of strength and toughness among the blends.…”
Section: Materials Joined Using Hot Meltsmentioning
confidence: 99%
“…However, for steel pipes, the low adhesion between these polymers and steel represents a significant challenge. 12,13 To address this issue, epoxy has emerged as a promising option due to its superior adhesive properties to metallic surfaces 14,15 and economic justifications as the binder between HSS and pipe. The insufficient compatibility between pure polyolefins and epoxy compromises their adhesion issues, rendering the use of an intervening third material indispensable to produce a composite material that satisfies all essential criteria for HSS.…”
Section: Introductionmentioning
confidence: 99%
“…HSS can be applied directly on cement pipes. However, for steel pipes, the low adhesion between these polymers and steel represents a significant challenge 12,13 . To address this issue, epoxy has emerged as a promising option due to its superior adhesive properties to metallic surfaces 14,15 and economic justifications as the binder between HSS and pipe.…”
Section: Introductionmentioning
confidence: 99%